Exploring the nexus: materialism value scales, TPB constructs, and debt intentions among young Malaysian Muslims - Md Shariff, Anita; Mohammed, Mustafa Omar; Ariffin, Muhammad Irwan (UiTM Cawangan Terengganu, 2023)
Household debt can have detrimental effects on personal finances and society as a whole. The rise of consumerism has contributed to increasing levels of debt and financial instability. In predominantly Muslim nations like Malaysia, materialism can have distinct implications on debt behavior. This study employs the Materialism Values Scales to investigate the multifaceted influence of materialism on debt intentions among Malaysian Muslims by assessing its impact on three key dimensions of the Theory of Planned Behavior (TPB). 348 young adult Muslims participated in a self-administered survey. Partial Least Square Structural Equation Modeling was used to analyze the data. The findings indicate a high level of materialism among respondents and demonstrate that materialism significantly influences all three dimensions of TPB, with centrality showing a notable impact across all three dimensions. The results further show that only attitude and lack of self control significantly influence borrowing intention. The findings offer valuable insights into mitigating materialistic tendencies and fostering a culture of responsible borrowing, thereby promoting financial sustainability.